Mathematical Modelling And Simulation Of Heat Dispersion Due To Fire And Explosion - Lim, Wan Piang; Ahmad, Arshad (Penerbit UTM Press, 2002)
Fire and explosion are among the commonly occurring major hazards in the operation of chemical plants. In this paper, a mathematical model for heat dispersion in the event of an industrial fire and explosion is presented. The model is simulated numerically within MATLAB environment to provide both the time and space dependence of the heat flux and temperature using a finite difference method. Three classes of fire were considered. These are pool fire, flash fire and fireball following the event of Boiling Liquid Expanding Vapour (BLEVE). The simulation program that has been developed is employed to study the impact of the three types of fire hazard on a LPG storage facility at the Chemical Engineering Pilot Plant in the Universiti Teknologi Malaysia. The results obtained highlights the various hazard condition for all the three events, with fireball imposing the most severe condition by having safety distance of 300 meters away from the source of release, within which fatalities are expected.